Child social rejection/acceptance: relationship with emotional problems and emotional intelligence - Mateu-Martínez, Ornela (2014)
The aim of this study was to analyse the relationship of social acceptance/rejection whit anxiety-depressive symptomatology and emotional intelligence in Spanish children. The sample consisted of 94 students of Elementary School between 8 and 12 years. Results revelled the significant relationship between rejection index and symptomatology of social phobia, dysphoria and low self-stem, while the model for choices index is related whit social skills. In resume, social rejection is related whit emotional problems, whereas social acceptance does with emotional intelligence. This study suggests the relevance of developing socio-emotional competences programs to promote social acceptance and to prevent emotional disorders related with social rejection in childhood.